Eight Students' Courtesies to Teachers Pursuant to Islamic Teaching - Rahayu, Sutria; Adel, Samiullah; Burhanuddin, Burhanuddin (International Journal of Islamic Studies Higher Education, 2022)
Seeking knowledge is a noble practice that will make it easier for the seeker to go to heaven. Therefore it is important for a student to pay attention to manners when dealing with a teacher both in class and outside of class. Because according to scholars, a noble work must be done in a noble way as well. Even the Salaf past paid a lot of attention to manners in learning, so it is not surprising that knowing manners is more important than learning with a teacher. Precisely, this article will discuss how a student behaves towards the teacher in the context of learning both inside and outside the classroom. This article is written using a qualitative method with a content analysis approach, all data is taken from various sources that come from books, classics, theories and expert opinions. All the data that has been gathered is then analyzed thematically and described in a comprehensive and in-depth manner. Based on the author's conclusion, there are eight manners that students should have towards the teacher, the eight manners are i) always sincerely respect the teacher, ii) try to purify the heart, iii) Tawadu about the knowledge learned, iv) listen well to every teacher's explanation, v) not contradicting and interrupting the teacher's conversation, vi) always enthusiastic in learning, vii) always praying for the teacher and viii) always glorifying the teacher. To make it more interesting, all the results of this research will be discussed with the results of previous studies and the latest issues. The author hopes that this article can be a source of guidance for students and teachers in seeking knowledge and can also be a foundation for subsequent researchers to discuss this problem in different contexts and issues.